The many faces of political Islam - Mohammed Ayoob (2009)
The paper argues that the multiple manifestations of political Islam are primarily determined by discrete contexts, that the vast majority of Islamist movements operate peacefully within constitutional constraints, and that democratization leads not only to the moderation of Islamist political formations as they are forced to build coalitions but also to their fracturing into various parties that pursue different agendas. It will also look back into history to argue that the political and religious realms have for all practical purposes remained separate in the classical age of Islam and that the contemporary manifestations of political Islam are products of the encounter between Europe and the Muslim world during the colonial period. It will argue further that the nature of regimes in the Muslim world and the general thrust of American policy augment the legitimacy and popularity of Islamist movements among the populations of predominantly Muslim countries.